Karakteristik Penafsiran Alquran dan Tafsirnya Karya Tim Kementerian Agama Republik Indonesia - Muhammad Esa Prasastia Amnesti (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
This article will explore the characteristics of the Koran of the Ministry of Religion of the Republic of Indonesia, both in terms of historical formulation and interpretation models. This research is also motivated by the claims of several scholars who state that the interpretation or translation of the Koran from the Ministry of Religion tends to be misunderstood by ordinary people. Does this article aim to review several things related to the history of the formulation of the Koran by the Ministry of Religion of the Republic of Indonesia? What are the patterns and characteristics of the interpretation applied to the Koran of the Ministry of Religion of the Republic of Indonesia? The results showed that the source of the interpretation of the Koran from the Ministry of Religion of the Republic of Indonesia used naqli and aqli reasoning with the tahili (detailed) interpretation method and the Muqarin technique. The tendency of his interpretation emphasizes more on literary and social issues and reflects the tendency of interpretation of adab al-ijtima'i and fiqh. This interpretation product is not suitable for ordinary people because the cost is too expensive and tends to expose the opinions of scholars who require analysis.